Building A Rural Economic Area Through Cooperation Between Villages: A Case Study of Agrotourism-Based Rural Area Development in Banyumas, Indonesia - Bambang Tri Harsanto; Alizar Isna; Wahyuningrat Wahyuningrat; Tobirin Tobirin; Dwiyanto Indiahono (Jurnal Wilayah dan Lingkungan, 2022)
This study aims to evaluate the implementation of cooperation between villages based on agrotourism in the Kendeng Mountains, Somagede District, Banyumas Regency as a model for developing rural areas in Banyumas Regency. The research was conducted in three villages in Somagede District, i.e., Tanggeran, Klinting, and Kemawi, and served as a pilot project for rural area development. Qualitative method is conducted through meetings with informants from all village officials and tourism business actors in the three collaborating villages and members of the Rural Area Development Coordination Team. This study employs qualitative method utilizing in-depth interviews, observations, documentation, and focus group discussion (FGD), while the findings were analyzed using an interactive analysis model. The results showed that the cooperation between the villages of Kemawi, Klinting, and Tanggeran in developing agrotourism-based rural areas did not yield the expected results. The failure is due to the absence of cooperation norms among members, the identification of common needs that must be resolved through inter-village collaboration, and the low commitment of the village heads to prioritize and carry out all program plans. The cooperation also fails because of the lack of support from the local government during program implementation and the absence of monitoring and evaluation activities at each stage of the implementation of inter-village cooperation.